Eating when depressed, anxious, bored, or happy: An examination in treatment-seeking adults with overweight/obesity. (1st May 2023) - Braden, Abby; Barnhart, Wesley R.; Kalantzis, Maria; Redondo, Rachel; Dauber, Aubrey; Anderson, LaNaya; Tilstra-Ferrell, Emily L.
Abstract: Emotions that differ in valence are uniquely associated with eating. In our previous study with an online sample of adults with overweight/obesity, eating in response to depression was the type of emotional eating most closely associated with negative psychosocial correlates (Braden et al., 2018). The current study extended this research by examining associations between emotional eating types (eating in response to depression, anxiety, boredom, happiness) and psychological correlates among treatment-seeking adults. The present study was a secondary analysis of adults ( N = 63; 96.8% female) with overweight/obesity and self-identified emotional eating who completed a baseline assessment for a behavioral weight loss intervention. Emotional eating in response to depression (EE-depression), anxiety/anger (EE-anxiety/anger), and boredom (EE-boredom) were assessed with the revised Emotional Eating Scale (EES-R), and positive emotional eating (EE-positive) was assessed with the positive emotions subscale of the Emotional Appetite Questionnaire (EMAQ). The Eating Disorder Examination Questionnaire (EDE-Q), Binge Eating Scale (BES), Difficulties in Emotion Regulation Scale (DERS), and Patient Health Questionnaire-9 (PHQ-9; depressive symptoms) were also administered. Frequencies showed the most endorsed emotional eating type was EE-depression (44.4%; n = 28). Four multiple regression analyses examined associations between emotional eating (EE-depression, EE-anxiety/anger, EE-boredom, and EE-positive) and dependent variables (EDE-Q, BES, DERS, and PHQ-9). Results showed that depression was the emotional eating type most closely related to disordered eating, binge eating, and depressive symptoms. Eating in response to anxiety was closely related to emotion regulation difficulties. Positive emotional eating was related to less depressive symptoms. Exploratory analyses showed that lower levels of positive emotional eating were related to higher depressive symptoms among adults with greater emotion regulation difficulties. Researchers and clinicians may consider tailoring weight loss treatment based on unique emotions that trigger eating.